ANALISIS KEBIJAKAN KEUANGAN NEGARA DAN STABILITAS SISTEM KEUANGAN UNTUK PENANGANAN PANDEMI CORONA VIRUS DISEASE 2019 PERSPEKTIF SIYASAH DUSTURIYAH (STUDI PASAL 27 UNDANG-UNDANG NOMOR 2 TAHUN 2020 TENTANG PENETAPAN PERPU NOMOR 1 TAHUN 2020) - Etry Mike; Yusmita Yusmita; Eling Sinta (Fakultas Syari'ah Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2022)
Abstract: The issues studied in this thesis are: (1), How is the Analysis of State Financial Policy and Financial System Stability for Handling the Corona Virus Disease (Covid-19) Pandemic (Study of Article 27 of Law Number 2 of 2020 concerning the Stipulation of Perpu Number 1 Year 2020) (2), How is the Analysis of State Financial Policy and Financial System Stability for Handling the Corona Virus Disease (Covid-19) Pandemic (Study of Article 27 of Law Number 2 of 2020 concerning Stipulation of Perpu Number 1 of 2020) Siyasah Duturiyah's Perspective. The type of research in writing this thesis is normative research using a statutory approach and a conceptual approach. With this method, the author analyzes both Law No. 2 of 2020 concerning the stipulation of Perpu No. 1 of 2020 or supporting legal materials, in order to produce a study on State Financial Policy Analysis and Financial System Stability for Handling the Corona Virus Disease (Covid-19) Pandemic. (Study of Article 27 of Law Number 2 of 2020 concerning Stipulation of Perpu Number 1 of 2020). So as to produce research results, namely: (1) the corona virus disease pandemic, requires the president to issue a Perpu then at the next trial the DPR ratifies the Perpu into a Law, namely Law Number 2 of 2020, but when viewed from the material content, especially Article 27 This law contradicts the Constitution and other laws. (2) In the case of the corona virus disease pandemic, which made the head of state and al-tasyri'iyah ijtihad so as to issue Law no. 2 of 2020 concerning the Stipulation of Perpu No. 1 of 2020 considering that the benefit of the community is the main goal in terms of issuing these regulations.Keywords: Corona Pandemic; State finances; Siyasah Duturiyah.